Behavior and physiological parameters of piglets in the first 24 hours of life - F. L. M. Loureiro; M. O. Lima; P. S. Cella (Scientific Electronic Archives, 2018)
The objective was to evaluate the behavior and physiological parameters of piglets in the first 24 hours of life. The experiment was conducted in Siviero Granja in Clevelândia municipality in the state of Parana. Data were collected from 84 piglets distributed in a completely randomized design with two treatments (T1- sows and T2 gilts) with 3 females per treatment (repetitions) and 14 piglets each. We evaluated about behavior (sucking, sleeping and others to tivities), respiratory rate, rectal temperature and skin surface temperature (neck, shoulder and leg). The physiological data were submitted to variance analysis, adopting the F test at 5% probability. While behavioral data were assessed by non-parametric and expressed in frequency distribution graph statistics. There was no effect (P> 0.05) of the treatments for any of the evaluated physiological parameters. However, in both treatments it was observed that the piglets remained more than half the time asleep or performing other activities. It was concluded that nursing piglets must be created in breeders cells with side shields against crushing and should still be used, on the first day of life, stay longer in creep when not nursing.